From trust to action: influencer credibility and perceived green risk shape green purchase intentions on social media - Zhou, Baiyu; Abdullah, Zulhamri; Hashim, Norliana; Qi, Meng; Cai, Yingying (Redfame Publishing Inc., 2026)
As environmentally friendly products become increasingly visible worldwide, consumer adoption in developing markets remains uneven, particularly on social media. This study examines the psychological and informational factors that influence Chinese social media users’ intentions to purchase green products. Building on the Theory of Planned Behavior (TPB), a research model incorporating influencer credibility and perceived green risk was empirically tested. Survey data were collected from 506 Chinese adults and analyzed using structural equation modeling (SEM). The findings indicate that attitudes, subjective norms, and perceived behavioral control are significant predictors of green purchase intention. In addition, higher levels of influencer credibility strengthen these three psychological factors and directly enhance purchase intention. In contrast, perceived green risk negatively affects these psychological factors. Mediation analysis further demonstrates that the TPB components transmit the effects of influencer credibility and perceived green risk on green purchase intention. By highlighting the dual roles of digital trust and perceived risk, this study contributes to a deeper understanding of pro-environmental decision-making in emerging economies and provides practical implications for designing effective green marketing strategies in social media contexts.